1998
DOI: 10.1002/(sici)1097-0134(19980601)31:4<453::aid-prot11>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Density functional studies on herpes simplex virus type 1 thymidine kinase–substrate interactions: The role of Tyr-172 and Met-128 in thymine fixation

Abstract: The enzyme herpes simplex virus type 1 thymidine kinase (HSV1 TK) salvages thymidine into the DNA metabolism of the virus. In the active site, the thymine ring of the nucleoside binds in a pocket, formed by two residues, Tyr-172 and Met-128, in a sandwich-type orientation. To investigate the nature of the thymine-enzyme pocket interactions, we have carried out density functional theory calculations with gradient-corrected exchange-correlation functionals of models of the thymine-HSV1 TK adduct. Our calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…3b). This is in marked contrast to HSV1-tk where the base is sandwiched by an aliphatic and aromatic residue, Met-128 and Tyr-172, respectively, with Ile-100 also making some contacts (19,26,36). These differences in interactions with the pyrimidine ring result in the base binding in a significantly different position to that seen in the HSV1-tk structure.…”
Section: Resultsmentioning
confidence: 73%
“…3b). This is in marked contrast to HSV1-tk where the base is sandwiched by an aliphatic and aromatic residue, Met-128 and Tyr-172, respectively, with Ile-100 also making some contacts (19,26,36). These differences in interactions with the pyrimidine ring result in the base binding in a significantly different position to that seen in the HSV1-tk structure.…”
Section: Resultsmentioning
confidence: 73%
“…40,41 In this respect, it has been shown that methionines display mainly hydrophobic character, 40 at least in the context of artificial hairpin peptides where their measurements were made. In fact, it could be that the water molecules are actually stabilizing the cf2 conformations rather than the cf1 conformation by binding to sulfur.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was consistent with the study [32] that activity was retained only with phenylalanine at Tyr 172 of HSV-1 TK. On the basis of the information obtained from the density functional studies on HSV-1 TK, the substrate-Tyr 172 interaction is essentially an electrostatic force and was suggested to be involved in the substrate binding [48]. The three-dimensional structure of the HSV-1 TK showed the aromatic ring of the tyrosine residue at this position stacked on to the thymine ring, and Arg 163 (HSV-1 TK) formed the hydrogen bond with the hydroxy group of the tyrosine residue at this position [36].…”
Section: Discussionmentioning
confidence: 99%